Cascaded H-bridge Multilevel Inverter for Induction Motor Drive with Improved Grid Current Quality - Prayad Kongsuk; Sakdawut Boontua; Vijit Kinnares; Jongrak Boonseng (My University, 2021)
This paper presents the implementation of a drive system using a cascaded H-bridge multilevel inverter and multi pulse rectifier for grid current quality improvement. A 5-level inverter is controlled by using a carrier based sinusoidal PWM signals technique implemented on a C2000 microcontroller. A front end converter has grid current quality improvement by applying twelve-pulse rectifiers based on phase-shifting transformers to reduce lower order current harmonics which could be injected into power supply grid. The proposed system has been tested for driving a three-phase induction motor. The obtained results verify that the proposed system is able to drive the induction motor as well as a reduction in the distortion of the grid current which are satisfactory.
Keywords: Multilevel Inverters and Converters; Microgrid Control and Optimization; Advanced DC-DC Converters